PENERAPAN PEMBELAJARAN VIRTUAL BERBASIS ZOOM MEETING UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA ( Studi Pada Pelajaran Geografi Kelas X di SMA Negeri 1 Pagar Alam) - Ita Fitrianah; Bayu Insanistyo (UNIB Press, 2021)
The purpose of this research is to describe the implementation of virtual learning based on zoom meeting which has several positive effects on increasing students activities and learning achievement as well as to see its effectiveness of virtual learning based on zoom meeting on student achievement in Geography subject in class X at SMAN 1 Pagar Alam. This research uses classroom action research. The research subjects were students of class X IPS 1 which has 36 students as the PTK Class, the Experiment Class were students of class X IPS 2 which has 35 students, and the Control Class were class X IPS 3 which has 36 students. This classroom action research uses 2 cycles, each cycle has 2 meetings and each cycle consists some steps like planning, implementation, and observation. The data collection techniques used observation instruments, pretest and posttest questions. Student observer and teacher consisted of two people. To see the effectiveness of learning, an experiment was carried out, the result of learning were analyzed by t-test. The results of this study can be concluded that implementation of virtual learning based on zoom meeting is effective on increasing students activities and learning achievement in Geography subject in class X students at SMA Negeri 1 Pagar Alam